Contestation of Customary Law and Islamic Law in Inheritance Distribution: A Sociology of Islamic Law Perspective - Rasyid, Arbanur; Lubis, Rayendriani Fahmei; Saleh, Idris (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
In the Mandailing Natal community in North Sumatra, Indonesia, predominantly Muslim, inheritance distribution often deviates from Islamic law due to the influence of local customs. The kinship system of na tolu plays a significant role, causing a delay in inheritance distribution until both parents have passed and all heirs are either of legal age or married. This practice aims to preserve family harmony but highlights a tension between Mandailing customary law and Islamic law, complicating the pursuit of justice in inheritance matters. This study explores the interaction between Mandailing custom and Islamic law in inheritance distribution, examining how the two legal frameworks influence one another. The research adopts a qualitative, juridical approach and reveals that customary norms, especially Dalihan Na Tolu, tend to outweigh Islamic law. Traditional leaders and religious scholars are key mediators, facilitating compromise and adaptation in inheritance distribution. The study suggests that enhancing Islamic law education and fostering collaboration between traditional leaders and scholars could help harmonize local customs with Islamic principles, ensuring a fairer inheritance process.